2015
DOI: 10.3389/fnhum.2015.00613
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Roles of Dorsolateral Prefrontal Cortex and Frontal Eye Fields During Saccadic Eye Movements

Abstract: The dorsolateral prefrontal cortex (DLPFC) and the frontal eye fields (FEF) have both been implicated in the executive control of saccades, yet possible dissociable roles of each region have not been established. Specifically, both establishing a “task set” as well as suppressing an inappropriate response have been linked to DLPFC and FEF activity, with behavioral outcome measures of these mechanisms mainly being the percentage of pro-saccade errors made on anti-saccade trials. We used continuous theta-burst s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 83 publications
1
29
1
Order By: Relevance
“…In the motor cortex, 30 Hz cTBS resulted in a larger and more consistent decrease in MEP amplitude than 50 Hz cTBS (Goldsworthy et al, 2012). Saccadic delay has also been reported following 50 Hz cTBS over the FEF, however, involvement of executive control of saccades were found following prefrontal stimulation (Cameron, Riddle, & D'Esposito, 2015), suggesting the effect of TBS may be distinct in different brain regions. Beyond the motor cortex, Nyffeler et al targeted the FEF, which is in close proximity to the prefrontal cortex, and found prolonged saccadic delay following 30 Hz cTBS (Nyffeler et al, 2006b).…”
Section: Inter-individual Variability In the Response To Conventionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the motor cortex, 30 Hz cTBS resulted in a larger and more consistent decrease in MEP amplitude than 50 Hz cTBS (Goldsworthy et al, 2012). Saccadic delay has also been reported following 50 Hz cTBS over the FEF, however, involvement of executive control of saccades were found following prefrontal stimulation (Cameron, Riddle, & D'Esposito, 2015), suggesting the effect of TBS may be distinct in different brain regions. Beyond the motor cortex, Nyffeler et al targeted the FEF, which is in close proximity to the prefrontal cortex, and found prolonged saccadic delay following 30 Hz cTBS (Nyffeler et al, 2006b).…”
Section: Inter-individual Variability In the Response To Conventionmentioning
confidence: 77%
“…Beyond the motor cortex, Nyffeler et al targeted the FEF, which is in close proximity to the prefrontal cortex, and found prolonged saccadic delay following 30 Hz cTBS (Nyffeler et al, 2006b). Saccadic delay has also been reported following 50 Hz cTBS over the FEF, however, involvement of executive control of saccades were found following prefrontal stimulation (Cameron, Riddle, & D'Esposito, 2015), suggesting the effect of TBS may be distinct in different brain regions. As there has been no other study using 30 Hz iTBS in the prefrontal cortex or FEF, future studies are required to confirm and expand these findings.…”
Section: Inter-individual Variability In the Response To Conventionmentioning
confidence: 99%
“…The involvement of the PFC, especially highly affected regions such as the dorsolateral PFC (Cameron et al, 2015; Leon-Dominguez et al, 2015), in executive functions may account for the association between prenatal maternal cortisol and both verbal and non-verbal measure of cognitive ability. Tests of indirect effects indicated that cortical thickness did not underlie the observed association between prenatal maternal cortisol and child cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…However, if a saccade wasn't planned, the latency of the peak of HG activity was correlated with reaction times. This suggests that middle and superior frontal gyri are also involved in the execution of saccades (Cameron et al, 2015).…”
Section: Discussionmentioning
confidence: 97%